2018
DOI: 10.3389/fchem.2018.00175
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Oxidation of Acetone Over High Thermally Stable TiO2 Nanosheets With Exposed (001) Facets

Abstract: Anatase TiO2 (A-TiO2) usually exhibits superior photocatalytic activity than rutile TiO2 (R-TiO2). However, the phase transformation from A-TiO2 to R-TiO2 will inevitably happens when the calcination temperature is up to 600°C, which hampers the practical applications of TiO2 photocatalysis in hyperthermal situations. In this paper, high energy faceted TiO2 nanosheets (TiO2-NSs) with super thermal stability was prepared by calcination of TiOF2 cubes. With increase in the calcination temperature from 300 to 600… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 44 publications
(58 reference statements)
1
24
0
Order By: Relevance
“…Solar energy, as a clean energy, has been widely concerned. It is a very effective way to solve the problem of water pollution by using solar energy (George et al, 2015; Wang et al, 2017, 2018a; Qi et al, 2018a; Shi et al, 2018; Wei et al, 2018; Yan et al, 2018a,b; Zhong et al, 2018). Since Fujishima et al reported the phenomenon of water splitting for hydrogen production on TiO 2 photoanode (Fujishima and Honda, 1972), the study of semiconductor photocatalysts has become very popular (Tao et al, 2014; Wei et al, 2015; Wen et al, 2015; Park et al, 2016; Qi et al, 2017b, 2018b; Xia et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Solar energy, as a clean energy, has been widely concerned. It is a very effective way to solve the problem of water pollution by using solar energy (George et al, 2015; Wang et al, 2017, 2018a; Qi et al, 2018a; Shi et al, 2018; Wei et al, 2018; Yan et al, 2018a,b; Zhong et al, 2018). Since Fujishima et al reported the phenomenon of water splitting for hydrogen production on TiO 2 photoanode (Fujishima and Honda, 1972), the study of semiconductor photocatalysts has become very popular (Tao et al, 2014; Wei et al, 2015; Wen et al, 2015; Park et al, 2016; Qi et al, 2017b, 2018b; Xia et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 is the most investigated material in the semiconductor photocatalysis research field. However, due to the wide bandgap, it is only responsive to UV light, which greatly limits its photocatalytic efficiency (Cui et al, 2013; Shi et al, 2018). In recent years, many visible-light-driven semiconductors have been designed and applied in solar energy conversion research fields (Wang et al, 2014; Pan, 2016; Shao et al, 2017, 2018; Cheng et al, 2018, 2019; Marchal et al, 2018; Wolff et al, 2018; Yang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As a rule, PCO processes use a semiconductor material as catalyst. Nowadays titanium dioxide (TiO2) is hitherto one of the most used catalysts in photocatalysis both in gas phase and in liquid phase, due to its attractive characteristics being low production cost, nontoxicity and high photocatalytic activity the most relevant features [11,12,13] In previously reported works, usually TiO2 is irradiated with UV light coming from conventional (xenon or mercury) lamps as energy emitters to degrade different types of VOCs. In general, these lamps exhibit low energy, nearly homogenous efficiency and poor light penetration making the complete VOCs removal an overall inefficient process [14,15].…”
Section: Introductionmentioning
confidence: 99%